Exploring stakeholder perspectives regarding the implementation of competency-based medical education: A qualitative descriptive study - Dubé, Tim; Wagner, Maryam; Zaccagnini, Marco; Gomez-Garibello, Carlos (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Introduction: Competency-based medical education (CBME) offers perceived advantages and benefits for postgraduate medical education (PGME) and the training of competent physicians. The purpose of our study was to gain insights from those involved in implementing CBME in two residency programs to inform ongoing implementation practices.Methods: We conducted a qualitative descriptive study to explore the perspectives of multiple stakeholders involved in the implementation of CBME in two residency programs (the first cohort) to launch the Royal College’s Competence by Design model at one Canadian university. Semi-structured interviews were conducted with 17 participants across six stakeholder groups including residents, department chairs, program directors, faculty, medical educators, and program administrators. Data collection and analysis were iterative and reflexive to enhance the authenticity of the results.Results: The participants’ perspectives organized around three key themes including: a) contextualizing curriculum and assessment practices with educational goals of CBME, b) coordinating new administrative requirements to support implementation, and c) adaptability toward a competency-based program structure, each with sub-themes.Conclusion: By eliciting the perspectives of different stakeholder groups who experienced the implementation processes, we developed a common understanding regarding facilitators and challenges for program directors, program administrators and educational leaders across PGME. Results from our study contribute to the scholarly conversation regarding the key aspects related to CBME implementation and serve to inform its ongoing development and application in various educational contexts.